Myrcianthes (Myrtaceae) revisited: a new species, a new synonym, a lectotypification and an overview of its wood anatomy - Proença, Carolyn Elinore Barnes; Faria, Jair Eustáquio Quintino De; Oliveira, Marla Ibrahim Uehbe De; Staggemeier, Vanessa Graziele; Farias-Castro, Antônio Sérgio; Sonsin-Oliveira, Júlia (Phytotaxa, 2023)
Myrcianthes is a New World genus of Myrtaceae (Tribe Myrteae) with 38 currently accepted species that was monographed in 1992. This paper proposes a new species, Myrcianthes cruciata from Northeastern Brazil (Bahia, Ceará and Sergipe), the synonymization of M. cavalcantei under M. fragrans and the lectotypification of the former name. Myrcianthes cruciata is similar to M. pseudomato but differs in the longer peduncles, 3.5–5 cm (2–4 cm in M. pseudomato) and greater number of ovules per locule, c. 15–30 (15–20 in M. pseudomato), as well as the morphology of the embryo, which is reniform in M. cruciata and strongly invaginated in the middle (almost V-shaped) in M. pseudomato and also emerged in different lineage in the phylogeny. The wood anatomy of the new species is similar to other species of the genus: diffuse porous, with exclusively solitary vessels with high density, no vessel arrangement, with simple perforation plates, vessel-ray pits with distinct borders, similar to the intervessel pits in size and shape, apotracheal parenchyma, rays 1–3 cells wide, with disjunctive ray cells; no helical thickenings were observed in the vessels, nor any mineral inclusions in the axial or ray parenchyma.